2012
DOI: 10.1007/s00894-012-1705-8
|View full text |Cite
|
Sign up to set email alerts
|

Rational design of the survivin/CDK4 complex by combining protein–protein docking and molecular dynamics simulations

Abstract: Survivin, the smallest inhibitor of apoptosis protein (IAP), is a valid target for cancer research. It mediates both the apoptosis pathway and the cell cycle and has been proposed to form a complex with the cyclin-dependent kinase protein CDK4. The resulting complex transports CDK4 from the cytosol to the nucleus, where CDK4 participates in cell division. Survivin has been recognized as a node protein that interacts with several partners; disruption of the formed complexes can lead to new anticancer compounds.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…In this study, the results demonstrated the roles of apoptotic proteins in inhibition of alsterpaullone on HeLa cells. Mcl-1 is a short-lived protein because the PEST sequences present with the Bcl-2 family member, and it is an important anti-apoptotic protein [13, 14]. In the current study, we found that Mcl-1 protein was rapidly down-regulated and even undetectable as early as 2 h in HeLa cells.…”
Section: Discussionsupporting
confidence: 52%
“…In this study, the results demonstrated the roles of apoptotic proteins in inhibition of alsterpaullone on HeLa cells. Mcl-1 is a short-lived protein because the PEST sequences present with the Bcl-2 family member, and it is an important anti-apoptotic protein [13, 14]. In the current study, we found that Mcl-1 protein was rapidly down-regulated and even undetectable as early as 2 h in HeLa cells.…”
Section: Discussionsupporting
confidence: 52%
“…Therefore, activation of p53 can induce cell apoptosis by down-regulating the glucose metabolism level (Liu et al, 2015). In addition, Survivin is a newly discovered member of inhibitors of apoptosis proteins (IAPs) family, and can inhibit cell apoptosis mainly through inhibition of the activity of the caspase family (Selent et al, 2013). In this study, with TSI treatment, the relative expression of NF-κB was approximately 0.53 times that of the control, the mRNA expression of p53 was significantly increased, while the expression of Survivin was significantly decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Selent et al also studied protein-protein binding by producing short MD simulations of 20 ns to refine a predicted complex between survivin/CDK4 [31].…”
Section: Protein-protein Binding Studiesmentioning
confidence: 99%